Peace on earth : the role of religion in peace and conflict studies - Matyók, Thomas, 1953- (Lexington Books, 2014)
Peace on Earth: The Role of Religion in Peace and Conflict Studies provides a critical analysis of faith and religious institutions in peacebuilding practice and pedagogy. The work captures the synergistic relationships among faith traditions and how multiple approaches to conflict transformation and peacebuilding result in a creative process that has the potential to achieve a more detailed view of peace on earth, containing breadth as well as depth.